Facile Synthesis of Valsartan and Ribose Prodrug and Studying its Influence on the Pancreatic Lipase - Abdulrazzaq, Khalidah M.; Khalil , Thaaer; Mahir , Firas Tahir (South Eastern European Journal of Public Health, 2024)
Valsartan is a widely used drug that belongs to the type of angiotensin receptor blockers generally specified to control high blood pressure (hypertension) and heart failure. In the present work, a new ester prodrug utilizes ribose sugar as a carrier for the valsartan through an esterification reaction. The synthesized compound was characterized by the FT-IR and 1H NMR spectroscopic. The investigation furthermore involved measuring the activity of the lipase enzyme in the blood serum of individuals with high blood pressure and healthy individuals and purifying the lipase enzyme utilizing gel filtration technology. Besides, the investigation studied the kinetics of the lipase enzyme, the impact of various substrate concentrations, the impact of pH and optimal temperature on the enzyme's activity, and the impact of reaction time on the enzyme's effectiveness. It was found that the effectiveness of the lipase enzyme reduced with raising the concentration of the synthesized compound, and the sort of inhibition was determined as competitive.